(untitled) (The Pakistan Development Review, 2014)
Electricity theft is a common problem in many countries and energy worth billions of dollars is stolen annually from electricity grids. The problem has socioeconomic, political, environmental and technical roots, but the solution is generally sought solely through technical measures. This paper empirically investigates the effects of various factors including electricity price, per capita income, probability of detection, fines collected from offenders, weighted temperature index and load shedding, that may explain the theft. The study employed annual panel data obtained from nine electricity distribution companies in Pakistan for the period 1988–2010. The study estimates the Fixed Effects models through the least squares dummy variable (LSDV) technique and Generalised Method of Moments (GMM). Our results indicate that per capita income has significant negative and electricity price a positive effect on electricity theft with sufficiently high coefficient values. The probability of detection variable appears with a positive sign in both estimations indicating a poor deterrence. The results of LSDV show a positive impact of fine on conviction on electricity theft. But in GMM estimation, this variable appears with a right sign. The results from both models are robust in the case of load shedding and temperature variables. The findings show that economic variables are most significant in explaining electricity theft. The findings may also be applicable in other developing countries where hefty amounts of revenues are lost due to electricity theft. Keywords: Electricity Theft, Fixed Effects Model, Pakistan